Identifikasi Timbulan Sampah Non-Organik Di Pulau Soop Distrik Sorong Kepulauan, Kota Sorong, Papua Barat Daya - Melkior Tigi; Melani Manurung; Roger R Tabalessy; Dwi Indah Widya Yanti; Melisa Ch Masengi; Gulam Arafat; Indrie Hapsari Puspitaningtyas (INTEGRATED OF FISHERIES SCIENCE, 2025)
Indonesia is said to be one of the countries contributing to plastic waste in the world. Therefore, the Government through the Ministry of Maritime Affairs and Fisheries has launched a priority program for handling plastic waste in the sea as an effort to reduce plastic waste. One form of support in handling plastic waste is to identify the potential for research-based waste generation in coastal areas and small islands. This research was conducted on Soop Island, Sorong Islands District, Sorong City, Southwest Papua from October to November 2024 with the aim of analyzing and identifying non-organic waste by knowing the amount, weight, and density of waste. This research method uses qualitative and quantitative. Qualitative research methods include observation, visual analysis, literature studies, and interviews. For quantitative methods calculating the amount of waste based on type per unit area. From the results of the study, it is known that the non-organic waste identified on Soop Island consists of plastic, plastic foam/styrofoam, glass and ceramics, metal, paper and cardboard, rubber, and other materials. The type of plastic waste dominates the most with a density of 8.33 pcs/m2 with a waste weight reaching 238.75 gr/m2. Meanwhile, the lowest waste density is in the paper and cardboard waste type with a density of 0.03 pcs/m2 with a weight of 2.38 gr/m2.